Can atrial fibrillation with a coarse electrocardiographic appearance be treated with catheter ablation of the tricuspid valve–inferior vena cava isthmus? Results of a multicentre randomised controlled trial. Issue 6 (29th November 2006) - Gupta, Dhiraj; Earley, Mark J; Haywood, Guy A; Richmond, Laura; Fitzgerald, Melissa; Kojodjojo, Pipin; Sporton, Simon C; Peters, Nicholas S; Broadhurst, Paul; Schilling, Richard J
Abstract : Objective: To see if strategy of ablating the tricuspid annulus–inferior vena cava isthmus (TV–IVC) is superior to electrical cardioversion to prevent recurrences in patients with coarse atrial fibrillation. Design: Prospective randomised controlled multicentre study. Setting: Four tertiary referral hospitals in the UK. Patients: 57 patients with persistent coarse atrial fibrillation (irregular P waves ⩾0.15 mV in ⩾1 ECG lead). Interventions: Patients were randomised to receive external cardioversion (group A, n = 30) or TV–IVC ablation +/− DC cardioversion (group B, n = 27). Main outcome measures: Cardiac rhythm, scores on quality of life and symptom questionnaires were assessed at 4, 16 and 52 weeks after the procedure. Results: 20 (67%) patients in group A and 19 (70%) patients in group B were in sinus rhythm immediately after their index procedure. At 4, 16 and 52 weeks, the number of patients in sinus rhythm were 5, 3 and 2 in group A and 3, 3 and 1 in group B (p = NS). The quality of life and symptom questionnaire scores were similar in the two groups at each period of follow-up, although they were significantly better for sinus rhythm than for atrial fibrillation at each follow-up visit. Conclusions: As a first-line strategy, TV–IVC ablation offers no advantages over direct current cardioversion for the management of coarse atrial fibrillation.